Primary Perianal Malignant Melanoma in a Dog - Combination Therapy - Rossi, Ygor Amaral; Ribeiro, Leticia; Medeiros, Regina Mendes; Spugnini, Enrico; Alves, Carlos Eduardo Fonseca [UNESP]; Anjos, Denner Santos dos (Universidade Federal do Rio Grande do Sul, 2022)
Background: Melanocytic neoplasm can arise from melanocytes in any location of the body. Malignant melanoma (MM) has a poor prognosis in dogs and presence of lymphvascular invasion, distant metastasis, or mitotic activity present prognostic value. Primary melanoma affecting the gastrointestinal tract has been rarely reported in veterinary literature, thus the prognosis affecting gastrointestinal tract is unknown. Electrochemotherapy (ECT) is an effective local treatment which combines chemotherapeutic drugs mainly bleomycin or cisplatin followed by the delivery of permeabilizing electrical pulses However, other hydrophilic drugs seem to present an increase cytotoxic effect such as carboplatin. Case: A 9-year-old mixed-breed neutered dog was referred to a private clinic with a mass in the perianal region diagnosed as perianal melanoma. No metastasis was observed on abdominal ultrasound nor chest x-ray (3 views). Clinical signs noted were tenesmus, hemorrhagic discharge, weight loss and hyporexia. Considering the tumor volume (16.0 x 10.0 cm), a neoadjuvant ECT session was proposed. The authors opted for carboplatin (300 mg/m2, intravenously), administered over 20 min and cisplatin intratumorally (1 mg/cm3, equivalent to 1 mL/1cm3 total volume 20 mL) administered in the upper parts of the mass that could be reached while avoiding drug leakage. After administration, sequences of eight biphasic pulses, (100 microseconds), with a voltage ranging from 650-1,000V/cm (pulse generator Onkodisruptor®) using a hexagonal/ single pair and plate electrode were delivered. At day 30th, a partial response was observed accordingly to RECIST system, with tumor size of 5.0 x 5.0 cm (65.4 cm3). A second ECT session was performed with the same previous protocol, but with a decreased dosage of carboplatin (240 mg/m2 consistent with 20% reduction) due to adverse effects in the first session, resulting in stable disease at day 60th (30 days after second ECT). Then, we proposed a surgical excision of the mass including partial resection of ventral rectum with intraoperative ECT. Afterwards, it was observed fecal incontinence that did not resolved after time but did not significant cause a morbidity in the patient. Patient achieved a disease-free interval (DFI) of 700 days and survival time of 730 days. Unfortunately, patient died due to distant metastasis. Discussion: Surgery is still the cornerstone treatment for MM in dogs, regardless anatomic site. However, in perianal region, wide or radical local surgical excision is a challenge due to anatomic region which precluded most of the time to achieve complete margins. In this report, the origin of the tumors was not defined since no normal tissue was found surrounding tumors cells probably due to tumor invasion and destruction of surrounding tissue. Thus, based on the previous literature, this tumor could have been arisen from rectum wall or anal sac. The longer DFI and survival time from this patient is superior from the most veterinary cases in literature which combined different types of treatment such as surgery, chemotherapy, immunotherapy, palliative care or ECT. Neoadjuvant ECT leaded to a reliable approach for partial remission in order to perform a better surgical approach in this case report. To conclude, ECT may be an option for partial remission and local control in regions which anatomic limitation is a challenge for wide excision.
Keywords: bleomycin; carboplatin; cisplatin; electroporation; melanocytic tumor